The Impact of Prolonged Grief Disorder on Experiential Avoidance in Parentally Bereaved Emerging Adults and the Moderating Role of Coping Skills - Farooqui, Mahnoor; Maroof, Daniya Abdul; Abbas, Hira (Pakistan Journal of Humanities and Social Sciences, 2025)
A person's relationship with their parents is one of the most wonderful things that can happen to them. This study primarily focused on individuals who have lost this precious relation in childhood. The objective of the research was to explore the relationship between experiential avoidance and prolonged grief disorder (PGD) in parentally bereaved emerging adults, and to determine the moderating role of coping skills in relationship between experiential avoidance and PGD. The study was quantitative in nature and research design of the study was correlational experimental design. For this purpose, Brief Experiential Avoidance Questionnaire, Brief COPE Inventory, and PG13-r were used. The total of 200 participants who were parentally bereaved emerging adults (67 males and 133 females) from Karachi, Pakistan were recruited based on the inclusion and exclusion criteria. The results showed significant association between experiential avoidance and PGD. It concluded experiential avoidance is significantly a predictor of emotion-focused and avoidant-focused coping whereas, problem-focused coping skills play a moderating role between both the variables. The findings proved the type of coping style an individual use can determine experiential avoidance and PGD. This research conclusively provided parentally bereaved emerging adults will involve in experiential avoidance that will lead to any of the coping skills; problem-focused, emotion-focused, and avoidant-focused. This, in turn, may lead to PGD.